2017
DOI: 10.1007/s12185-017-2201-9
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of miR-196b-5p is significantly associated with the progression of myelodysplastic syndrome

Abstract: Myelodysplastic syndrome (MDS) is a clonal stem cell disorder characterized by ineffective hematopoiesis with a high risk of transformation to acute myeloid leukemia (AML). miRNAs function as tumor suppressors and oncogenes in various cancers and regulate the differentiation potential of hematopoietic stem and progenitor cells (HSPCs). It has been suggested that miRNAs may play an important role in progression of MDS. We analyzed bone marrow samples collected from MDS patients according to different risk strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…miR-490-5p inhibits cell proliferation, migration and invasion but miR-490-5p can promote apoptosis of Human hepatoma (Hep3B) cells by inhibiting Roundabout Guidance Receptor 1 (ROBO1) [31]. MiR-196b-5p overexpression may also be associated with a risk of conversion of myelodysplastic syndrome (MDS) to acute myeloid leukemia (AML) [32]. The target miRNAs ssc-miR-194b-3p, ssc-miR-184, ssc-miR-215, ssc-miR-874 were all down regulated.…”
Section: Discussionmentioning
confidence: 99%
“…miR-490-5p inhibits cell proliferation, migration and invasion but miR-490-5p can promote apoptosis of Human hepatoma (Hep3B) cells by inhibiting Roundabout Guidance Receptor 1 (ROBO1) [31]. MiR-196b-5p overexpression may also be associated with a risk of conversion of myelodysplastic syndrome (MDS) to acute myeloid leukemia (AML) [32]. The target miRNAs ssc-miR-194b-3p, ssc-miR-184, ssc-miR-215, ssc-miR-874 were all down regulated.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs simultaneously targeting intracellular pathways are involved in a broad range of (patho)physiologic processes. They are critical regulators of hematopoiesis and their aberrant expression has been associated with various types of leukemia [ 35 , 36 , 39 ] Their functional role in the context of MDS and sAML is under debate due to methodical differences and the source/material profiled for miRNA expression in both diseases [ 38 , 39 , 94 , 96 , 100 , 123 , 124 , 125 , 126 ]. Sorted CD34 + BM cells still comprise a heterogeneous cell population and not all neoplastic blasts in MDS and sAML express CD34 [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, these studies significantly differed with regard to the cellular source investigated. While some studies used unsorted BM cells [ 100 , 123 ] others examined mononuclear cells [ 38 , 39 ] [ 94 , 96 , 124 , 125 ] or CD34 + BM cells [ 126 ], respectively. It is noteworthy that each investigative approach has its own advantages and disadvantages.…”
Section: Clinical Relevance Of Mirnas In Mds and Amlmentioning
confidence: 99%
“…Analysis of literature data showed that miRNA expression profiles differ between early and advanced stages of MDS, suggesting the involvement of miRNAs in the pathogenesis of MDS and, consequently, in MDS-to-AML transformation [ 99 ]. The expression levels of miRNA-27a-3p, −150-5p, −199a-5p, −223-3p and miRNA-451a are reduced in the plasma of high-risk patients with MDS, while miRNA-196b-5p is enhanced in BM specimens from a higher-risk patient with MDS, suggesting that these miRNAs may be used as biomarkers predicting the risk of further transformation of MDS [ 100 , 101 ]. Elevated miRNA-661 and miRNA-125a are negatively correlated with survival in MDS [ 102 , 103 ].…”
Section: Mirna In the Prognosis Of Mdsmentioning
confidence: 99%